Case series of primary psychiatric skin disorders with multi-disciplinary approach - Lusiana, Lusiana; Prayogo, Rizky Lendi; Yusharyahya, Shannaz Nadia; Sitohang, Irma Bernadette S.; Bramono, Kusmarinah (Journal of General - Procedural Dermatology and Venereology Indonesia, 2020)
Background: The incidence of psychodermatologic diseases, a group of skin abnormalities associated with psychosomatic factor, are increasing recently. About 20-40% patients with skin symptoms have concurrent psychiatric problems which are often difficult to diagnose and treat. The new classification of primary psychiatric skin disorders are delusional disorders, obsessive-compulsive and related disorders, and factitious disorders. This classification could be used for effective treatment in each patient which involves multi-disciplinary approach, including dermatology, psychiatry and other discipline if necessary. Case Illustration: The first case was a 39-year-old unmarried female, with anemia and dermatitis artefacta occurred as wound due to blade cuts. Patient was with schizoaffective depressive type and was not under regular treatment. The second case was a 61-year-old male referred with unresolved prurigo nodularis for the past 30 years. After in-depth assessment, there were delusional parasitosis and neurotic excoriations disorders. The third patient was a 50-year-old female admitted with recurrent ulcer on her face. She was aware that the lesions were intentionally manipulated by her own fingers when she was depressed. Discussion: All patients were classified as primary psychiatric skin disorders with varied skin manifestations. Symptoms usually occurred when the patient was in the depression state or low compliance for the psychotropic drugs. Patients generally had poor insight and refused to be associated with psychiatric factors. Dermato-venereologists are expected to conduct early detection and treat this disease. Conclusion: It is important to approach psychocutaneous disease in multi-disciplinary manner, especially with the psychiatrist.